KNOWLEDGE, AWARENESS AND BEHAVIOUR TOWARD SUN EXPOSURE AMONG PHARMACY STUDENTS - Wan Nordini Hasnor Wan Ismail; Mohd Izani Othman; Suraya Sulaiman; Wan Nur Najihah Wan Zulkifli; Alia Syakirah Mohd Sukri; Nur Adila Zulkifli (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Background: Sunlight exposure has several health advantages, including sulphated vitamin D3 synthesis, enhanced cognitive function, supporting bone health, decreasing blood pressure, avoiding illness, and fostering positive mental health. Nevertheless, there are still taboo that relates sun exposure and skin cancer and this phenomenon makes people prefer staying indoor most of the time. Many international studies have been conducted to assess the public perceptions towards sun exposure. To date, there is scarce data on this topic among students in Malaysia. Objectives: This study aimed to assess the knowledge, awareness and behaviours towards sun exposure among the Diploma in Pharmacy students of Universiti Teknologi MARA (UiTM). Methods: An online cross-sectional study was conducted from March to May 2022 among the Diploma of Pharmacy students in UiTM Cawangan Pulau Pinang. A self-administered questionnaire was constructed in Google Forms consisting of multiple-choice closed-ended questions. Descriptive analysis were used to summarise the sociodemographic profile of the respondents while Chi-square test was used to explore the association between sociodemographic variables and adequacy of knowledge, awareness and behaviour. Result: A total of 176 students with a 100% response rate participated in the study. Majority of the students had high knowledge on the benefits of sun exposure and high awareness on harmful effects of lacking sun exposure. They also showed slightly positive behaviour towards sun exposure. Conclusion: Education and awareness regarding the effects of sun exposure on human health, particularly among students, has to be more progressive. With good instruction and understanding from everyone, we could inform the public about the benefits of sun exposure and encourage them to practise it safely.